Real Estate Investment Trusts (REITS): A new business model in the FTSE100. Issue 4 (December 2015) - Haslam, Colin; Tsitsianis, Nick; Andersson, Tord; Gleadle, Pauline
Highlights: REITs are a relatively new business model in the FTSE 100. REITs investors qualify for tax concessions so long as 90 percent of profits are distributed. Fair value accounting (FVA) is a key element governing a REITs financial viability. Fair value accounting (FVA) triggered significant financial instability in UK REITs. Abstract: This paper is about the Real Estate Investment Trust (REIT) business model. REITs benefit from tax concessions and Fair Value Accounting (FVA) practices. REITs distributing over 90 percent of profits can obtain tax concessions for their shareholders. This encourages profit distribution at the expense of accumulating retained earnings in shareholder equity. The financial viability of REITs depends upon FVA because this records holding gains when property values are increased. These holding gains can be employed to generate additional financial leverage. However, REITs are exposed to property market volatility and this can quickly undermine solvency, credit ratings and financial stability.